(untitled) (Boletín Epidemiológico Semanal, 2023)
Introduction: In Spain, the severe acute respiratory infection sentinel surveillance system (SiVIRA), the individualized notification of COVID-19 cases (SiViES) and the care capacity system (CMC) overlapped in time. The objective is to compare the estimated rates of hospitalized COVID-19 cases, as well as their severity, in the three systems. Method: The weekly rate of COVID-19 hospitalization (per 100,000 inhabitants), was estimated both overall and by age groups, as well as the proportion of ICUs and mortality among hospitalized patients in 3 periods: P1=Weeks 40/2021-12/2022; P2=Weeks 13/2022-39/2022; P3=Weeks 40/2022-08/2023. Results: The three systems showed similar trends, but the average rate (cases/100,000) was higher in all periods in the CMC (P1=11.8; P2=10.7; P3=5.3), than in SiViES (P1=7.7; P2=7.5; P3=3.7) and SiVIRA (P1=6.4; P2=5.6; P3=1.8). The greatest difference was in the 5-14 and 15-44 years age groups (2.2-2.3 times higher in SiViES vs. SiVIRA), where the SiVIRA rates were also more unstable, and the smallest difference in the ≥45 years age groups (1.3 times higher in SiViES vs. SiVIRA). No systematic differences were observed in the proportion of cases requiring ICU (range in the different periods: SiVIRA 3.8-9.8%; SiViES 4.5-7.7%; CMC 5.2-9.7%) nor in mortality (range: SiVIRA 8.2-14.0%; SiViES 6.2-12.1%). Conclusions: SiVIRA, SiViES and CMC were equally valid for monitoring hospitalization rates due to COVID-19. SiVIRA implemented a more specific case identification, resulting in lower estimated rates, especially in age groups <45 years and during the last season 2022/23.